The “ḥadīṯ literature”: What is it and where is it? - Burge, Stephen R. (Arabica, 2018)
This article seeks to explore what the ḥadīṯ literature is from a theoretical perspective. Developing ideas first formulated by Andrew Newman, it will be argued that the “ḥadīṯ literature” is an abstract concept, which, subsequently, raises a number of issues and questions. Using a comparison of two works on ǧihād as a case study—al-Biqāʿī’s (d. 885/1480) Ḏayl al-istišhād bi-āyāt al-ǧihād and al-Suyūṭī’s (d. 911/1505) Arbaʿūn ḥadīṯan fī faḍl al-ǧihād—questions around the “ḥadīṯ literature” and what it is will be raised. The discussion will focus on the way in which the ḥadīṯ found in ḥadīṯ collections are affected by a compiler’s own personal discourse and historical context. It will be argued that a paradox emerges in which ḥadīṯ are both part of an abstract, atemporal “ḥadīṯ literature,” but, at the same time, rooted in the theological and historical context of the compiler.